Study on the Coupling Law between Pore-Scale Fluid Flow Capacity and Pore-Throat Configuration in Tight Sandstone Reservoirs - Jie Gao; Hu Wei; Ran Zhou; Qiang Ren; Tao Tian; Bo Ning; Xiaojun Ding; Zhifeng Zhang (Geofluids)
As for the tight sandstones, pore-scale fluid flow ability is one of the most fundamental parameters that determine potential development capacity when compared to conventional reservoirs due to relatively tiny spaces. The determination of pore-throat structures and their impact on fluid flow behavior could improve the forecast ability for development. Therefore, the main purpose of this paper is to study the effects of differences in microscopic pore structures on moveable fluid saturation in tight sandstone reservoirs. Casting thin sections (CTS), scanning electron microscope (SEM), constant-rate mercury injection (CRMI), nuclear magnetic resonance (NMR), etc. are used as experimental methods to qualitatively describe the differences in accumulation space types and to quantitatively compare and analyze the differences in microscopic pore structures between reservoirs for Chang 6 formation in the Jiyuan and Heshui areas. The different characteristic parameters are chosen to analyze their correlations with moveable fluid saturation. Thus, as a result, due to good correlations with moveable fluid saturation, parameters such as throat radius, pore-throat radius ratio, and pore-throat amount allocation ratio are chosen to characterize the differences in microscopic pore structures between reservoirs in those areas. Differences in throat radius, pore-throat radius ratio, and a pore-throat amount allocation ratio of microscopic pore structure of Chang 6 members in these two areas have led to differences in moveable fluid saturation to some extent. This research provided the evidence about the coupling law between pore-scale fluid flow capacity and pore-throat configuration in tight sandstone reservoirs, and the results can provide theoretical guidance for field development of oil and gas fields.